REFLECTIONS ON COMPUTER-RELATED RISKS. - Neumann, Peter G. (Communications of the ACM, 2008)
The article discusses the low trustworthiness of computer operating systems and application software. Buffer overflows and faulty bounds checks continue to plague applications. Denial-of-service attacks are hard to defend against. Strong cryptography is difficult to implement, and sound software engineering principles are only casually observed. The author began writing a periodical column about these and other risks in 1990, yet the problems seem no less diminished today. This is particularly troublesome in light of how information technology is relied upon for ever more and critical applications.